PERBANDINGAN PENERAPAN MODEL DIRECT INSTRUCTION DENGAN MODEL COURSE REVIEW HORAY TERHADAP HASIL BELAJAR MATERI PECAHAN KELAS 2 SD - Risa Aulia Tanti; Ilmawati Fahmi Imron; Aan Nurfahrudianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research was conducted based on the results of observations that have been carried out at SDN 1 Begadung which showed that the value of student learning outcomes in the subject of mathematics on fraction material in class 2 was below the average value that had been determined. In learning activities, teachers used the Direct Instruction learning model with the lecture method. The solution to this problem is to apply the Course Review Horay learning model with the help of fraction card media. The purpose of the research conducted was to determine the effect of implementing the learning model on learning outcomes. This study uses a quantitative approach with a Quasy Experimental Design research design. The subjects of this study were all 25 students in class 2A and all 25 students in class 2B. The sampling technique was Non Probability Sampling. The data collection technique used an instrument in the form of 15 multiple choice questions. The test results in the experimental class Sig. 0.000 which explains that there is an effect of implementing the Course Review Horay model on learning outcomes, while the test results in the control class Sig. 0.000 which explains that there is an effect of implementing the Direct Instruction model. After testing using the independent Sample t-test, the results of Sig. 0.006 which explains that there are differences in the application of learning models to learning outcomes.